1‐Hydroxy‐xanthine derivatives inhibit the human Caf1 nuclease and Caf1‐containing nuclease complexes via Mg2+‐dependent binding. Issue 4 (7th March 2019) - Airhihen, Blessing; Pavanello, Lorenzo; Jadhav, Gopal P.; Fischer, Peter M.; Winkler, Gerlof Sebastiaan
Abstract : In eukaryotic cells, cytoplasmic mRNA is characterised by a 3′ poly(A) tail. The shortening and removal of poly(A) tails (deadenylation) by the Ccr4‐Not nuclease complex leads to reduced translational efficiency and RNA degradation. Using recombinant human Caf1 (CNOT7) enzyme as a screening tool, we recently described the discovery and synthesis of a series of substituted 1‐hydroxy‐3, 7‐dihydro‐1 H ‐purine‐2, 6‐diones (1‐hydroxy‐xanthines) as inhibitors of the Caf1 catalytic subunit of the Ccr4‐Not complex. Here, we used a chemiluminescence‐based AMP detection assay to show that active 1‐hydroxy‐xanthines inhibit both isolated Caf1 enzyme and human Caf1‐containing complexes that also contain the second nuclease subunit Ccr4 (CNOT6L) to a similar extent, indicating that the active site of the Caf1 nuclease subunit does not undergo substantial conformational change when bound to other Ccr4‐Not subunits. Using differential scanning fluorimetry, we also show that binding of active 1‐hydroxy‐xanthines requires the presence of Mg 2+ ions, which are present in the active site of Caf1. Abstract : We describe the use of AMP detection to measure the biochemical activity of deadenylase enzymes and show its utility by determining the inhibitory activity of 1‐hydroxy‐xanthines versus the Caf1 subunit, or subcomplexes of Ccr4‐Not containing the Caf1 and Ccr4 subunits. In addition, we describe the use of differential scanning fluorimetry to investigate the binding mode of 1‐hydroxy‐xanthines to Caf1.